PKM PENERAPAN PLTS PADA KAWASAN PERTANIAN HIDROGANIK PADI DI BENGKEL MIMPI KABUPATEN MALANG - Budiyanto, Hery; Setiawan, Aries Boedi; Siswati, Aris (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Currently, rice farming land is getting narrower because it is pressed for housing. Ways are needed to utilize narrow land to develop a rice farming system, including hydrogenic farming, which is an organic cultivation system by planting rice on humus soil in plastic cups planted in a row of paralon pipes above fish ponds, integrating a hydro system (water circulation) nutritious and organic systems (without chemical fertilizers). This Community Partnership Program aims to deal with the problems experienced by service partners, namely the Self-help Agricultural and Rural Training Center